New Urea and Thiourea Derivatives of Piperazine Doped with Febuxostat: Synthesis and Evaluation of Anti-TMV and Antimicrobial Activities - Reddivari Chenna Krishna Reddy; Syed Rasheed; Devineni Subba Rao; Shaik Adam; Yellala Venkata Rami Reddy; Chamarthi Naga Raju (The Scientific World Journal)
A series of new 4-(5-(3-cyano-4-isobutoxyphenyl)-4-methylthiazole-2-carbonyl)-N-(substituted phenyl)piperazine-1-carboxamides 8(a–e)/carbothioamides 8(f–j) were accomplished for biological interest by the simple addition of active functionalized arylisocyanates 7(a–e)/arylisothiocyanates 7(f–j) with 2-isobutoxy-5-(4-methyl-2-(piperazine-1-carbonyl)thiazol-5-yl)benzonitrile (4). Compound 4 was synthesized in high yields (94%) by the condensation reaction of febuxostat (1) with piperazine using a selective reagent such as propylphosphonic anhydride (T3P). Antiviral activity against Tobacco mosaic virus (TMV) and antimicrobial activity of the synthesized compounds were evaluated. Biological data revealed that 4-nitrophenyl substituted urea 8d, and 3-bromophenyl substituted thiourea 8f exhibited promising antiviral activities. Moreover, 4-fluorophenyl substituted urea 8a, 4-nitrophenyl substituted urea 8d, 3-bromophenyl substituted thiourea 8f, and 2,4-dichlorophenyl substituted thiourea 8j exhibited potent antimicrobial activity.